Understanding and Kinetic Modeling of Complex Degradation Pathways in the Solid Dosage Form: The Case of Saxagliptin - Blaž Robnik; Blaž Likozar; Baifan Wang; Tijana Stanić Ljubin; Zdenko Časar (MDPI AG, 2019)
Drug substance degradation kinetics in solid dosage forms is rarely mechanistically modeled due to several potential micro-environmental and manufacturing related effects that need to be integrated into rate laws. The aim of our work was to construct a model capable of predicting individual degradation product concentrations, taking into account also formulation composition parameters. A comprehensive study was done on active film-coated tablets, manufactured by layering of the drug substance, a primary amine compound saxagliptin, onto inert tablet cores. Formulation variables like polyethylene glycol (PEG) 6000 amount and film-coat polymer composition are incorporated into the model, and are connected to saxagliptin degradation, via formation of reactive impurities. Derived reaction equations are based on mechanisms supported by ab initio calculations of individual reaction activation energies. Alongside temperature, relative humidity, and reactant concentration, the drug substance impurity profile is dependent on micro-environmental pH, altered by formation of acidic PEG degradation products. A consequence of pH lowering, due to formation of formic acid, is lower formation of main saxagliptin degradation product epi-cyclic amidine, a better resistance of formulation to high relative humidity conditions, and satisfactory tablet appearance. Discovered insights enhance the understanding of degradational behavior of similarly composed solid dosage forms on overall drug product quality and may be adopted by pharmaceutical scientists for the design of a stable formulation.